THERMAL DIFUSIVITY OF SWEET POTATO FLOUR MEASURED USING DICKERSON METHOD - I. K. Tastra; Erliana Ginting; Ratnaningsih . (Jurnal Keteknikan Pertanian, 2006)
Abstract Sweet potato (Ipmoea batatas I.) is one the carbohydrate sources in indonesia that can be used both for food and industry purposes. To support the utilization of sweet potato as flour, it is imperative to develop a drying system that can improve its quality. A preliminary study using an improved variety, namely Sari, was conducted to determine its floure thermal diffusivity (a ),  an imprortant parameter in developing drying process. The experiment was run according to Dickerson method using sweet potato flour at different levels of moisture content (5.05-5.97% wet basis) and temperatures (23.7 -40.9 oC) this method  used an apparatus based on transient heat transfer condition requiring only a time- temperature data. At the levels of moisture and temperature studied, the thermal diffusivity of sweet potato flour could be expressed using a linear regression model, a= 10-9 M.T + 9X 10-9( R2=0.9779). the average value of the thermal diffusivity sweet potato flour was 1.72 x 10-7 m2/s at a moisture level of 5.51 % wet basis and temperature of 29.58 oC. Similar studies are needed for different varieties or cultivars of sweet potato as well at a wide range of moisture content and temperature content and temperature levels. Keyword: sweet potato flour, thermal diffusivity, Dickerson Method.